Effects of Particle Size Distribution on Loading Performance - Ali Kahriman; Umit Ozer; Abdulkadir Karadogan; Kagan Ozdemir; Gungor Tuncer; Ertugrul Kaya (International Society of Explosives Engineers, 2008)
The results of bench blasting on quarries, have important influences on the performance of subsequent mining activities such as loading, hauling, crushing, grinding etc., and the total costs of that mine. Drilling and blasting is an important step in mine producing chain and its results such as fragmentation, muckpile shape and looseness, dilution, damage and rock softening effect the efficiency of downstream processes. Within the scope of this study, the three different hydraulic excavators’ working performances have been studied considering the particle size distribution after bench lasting at a quarry in Istanbul Turkey. Five shots have been realized on the quarry and average particle size of muckpile after each shot were assessed by digital image analysis method. Bucket loading times have been measured by stopwatch study after five shots. Excavator bucket loading times were also estimated by bucket loading time estimation formula which was published in ISEE 2007 Conference, Ozdemir et al. 2007. Estimated and measured times have been statistically analyzed and the accuracy rate of formula has been determined for five events.